Deafness and Pastoral Care in the Middle Ages - Kuuliala Jenni; Välimäki Reima (Routledge, 2025)
This chapter discusses medieval pastoral care and theological views of deafness and of deaf people’s ability to participate in religious life. Focusing in particular on confessors’ manuals, and challenging the often black and white interpretations of Augustine’s views on (congenitally) deaf people’s intelligence and religiosity, the article demonstrates how the authors of these manuals advised parish priests to take care of deaf people’s marriage and confession sacraments. Since the sacrament of marriage was a matter of free will, the writers stated that so long as such will could be expressed, there was no barrier to the deaf marrying. As for confession and the necessary sentiment of contrition, the deaf were also allowed and expected to participate in this important sacrament. However, the lack of sophisticated sign language posed a challenge to pastoral care. The chapter uncovers the various means of, and challenges to, teaching the deaf about the inner meanings of religious sacraments and rites.
Disability in Medieval Christian Philosophy and Theology